Diffusion analysis of full digitalization innovation in Republika West Java - Soraya, Dea Alvi; Sugiana, Dadang; Bakry, Gema Nusantara (Universitas Bunda Mulia, 2024)
This research discusses the adoption of full digitalization innovations in Republika Newspaper, West Java, after discontinuing the Harian Republika Newspaper printing at the end of 2022. This research analyzes how Republika West Java journalists adjust to changes regulations increasing workload. Researchers used qualitative research methods. Data was collected through interview and observation techniques that refer to five determining attributes of innovation adoption: Relative Advantage, Compatibility, Complexity, Triability, and Observability. Based on the findings obtained, in general, the five meanings have a role and simultaneously influence on the adaptability and motivation of the work of Republika West Java journalists.